Beyond faith: social marginalisation and the prevention of radicalisation among young Muslim Australians. Issue 2 (3rd April 2019) - Bull, Melissa; Rane, Halim
ABSTRACT: Counterterrorism responses in Australia have mirrored trends in other nations with a focus on pre-emption, including the criminalisation of activities defined as preparatory offences. Security-based transnational approaches to combat terrorist activity and propaganda alone are ineffective. Sometimes security measures can actually damage efforts to counter the appeal and take-up of violent extremism. While such measures should be used in domestic contexts where threats are critical or imminent, robust soft power initiatives are needed. Even though governments recognise the importance of soft power approaches, public discourse and commentary frequently reproduces negative stereotypes of young Muslim people linking them, through their religion, in negative ways to radicalisation and terrorism. This article describes empirical research investigating the impact of such discourses on the lives of young Muslim Australians. It demonstrates how dominant public discourse and counter-narratives add to feelings of marginalisation, even in those who are well integrated into Australian society. It argues that such social marginalisation contributes to the conditions of possibility for radicalisation and concludes by discussing some of the ways that young Muslim Australians maintain resilience in an environment that could easily be perceived as increasingly hostile and divisive.